The Public Authorities Protection Act 1948: A Case for Repeal - Balan, Sujata (Journal of Malaysian and Comparative Law, 2007)
The Public Authorities Protection Act 1948 (Act 158) (Revised 1978) is a short Act containing only three sections. Its main provision is s 2 which prescribes a short limitation period of 36 months if an intended defendant is a public authority, and if the act, neglect or default complained of was done in the execution or intended execution of any written law or of a public duty or statutory duty or authority. In this paper, the writer attempts a critical examination of the 1948 Act with the purpose of highlighting its anomalies and deficiencies and to put forward a case for its repeal.